122k views
1 vote
For f(x)=-2x^3-4x^2+3x-8 , use the remainder theorem to determine f(-1).

User Nidhoegger
by
5.8k points

2 Answers

5 votes

Hello

- 13

Explanation step by step:

x = - 1

f (x) = remainder to be divided by (x + 1)

f (- 1) = - 2 (- 1) ³ - 4 (- 1) ² + 3 (- 1) - 8

= 2 - 4 - 3 - 8 = - 13

The rest of the division of f (x) / (x + 1) = -13

User Mayday
by
5.9k points
3 votes

Answer:

- 13

Explanation:

Substitute x = - 1 into f(x) to obtain the remainder on dividing by (x + 1)

f(- 1) = - 2(- 1)³ - 4(- 1)² + 3(- 1) - 8

= 2 - 4 - 3 - 8 = - 13

Thus the remainder on dividing f(x) by (x + 1) is - 13

User Saurabh Sengar
by
6.0k points